Corrigendum: Adaptation of The Diabetes Distress Scale on a Russian-speaking sample of patients with type 1 and type 2 diabetes mellitus (Diabetes mellitus. – 2024. – Т. 27. – №5. https://doi.org/10.14341/DM13150) - N. V. Likhodey; V. E. Epishin; M. F. Kalashnikova; A. M. Kaurova; M. V. Tulupova; Yu. P. Sych; I. B. Bondareva (Сахарный диабет)
A corrigendum on «Adaptation of The Diabetes Distress Scale on a Russian-speaking sample of patients with type 1 and type 2 diabetes mellitus» authored by Natalia V. Likhodey, Vitalii E. Epishin, Marina F. Kalashnikova, Aleksandra M. Kaurova, Margarita V. Tulupova, Yulia P. Sych, Irina B. Bondareva (2024). Diabetes Mellitus. 27(5). https://doi.org/10.14341/DM13150.An error was made in the article. In the final version of the article, the order of questions in Figure 1 and Table 4 does not correspond to the version of the questionnaire used during data collection. This discrepancy occurred because two English versions of the questionnaire, differing in the order of questions 1 and 2, were initially used in the study.The correct order of questions in The Diabetes Distress Scale is as follows:Question 1: Feeling that diabetes taking up too much of my mental and physical energy every day.Question 2: Feeling that my doctor doesn’t know enough about diabetes and diabetes careThe editorial board regrets this error. The original version of the article has been replaced.